2018
DOI: 10.1007/s00268-018-4671-1
|View full text |Cite
|
Sign up to set email alerts
|

Application of the AAST EGS Grade for Adhesive Small Bowel Obstruction to a Multi‐national Patient Population

Abstract: Study type Retrospective multi-institutional cohort study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 43 publications
0
9
0
1
Order By: Relevance
“…de 59 años, que concuerda con los estudios de Hernández et al 16 y Matsushima et al 17 , aunque otros estudios describen la mayoría de los casos en pacientes mayores de 65 años 18,19 .…”
Section: Discussionunclassified
“…de 59 años, que concuerda con los estudios de Hernández et al 16 y Matsushima et al 17 , aunque otros estudios describen la mayoría de los casos en pacientes mayores de 65 años 18,19 .…”
Section: Discussionunclassified
“…An NSQIP study that included a subset of patients with all‐cause SBO at 13 voluntary USA and Canadian institutions reported lower unadjusted mortality rates of 3·3 per cent in operated patients and 4·5 per cent in the non‐operative group. Another recent multinational retrospective study limited to four centres reported a mortality rate of just 2 per cent across both operated and non‐operated patients with adhesive SBO; however, the primary objective of that study was retrospective validation of a proposed risk prediction tool and it may have been subject to selection bias. Both studies had non‐surgery rates exceeding 60 per cent.…”
Section: Discussionmentioning
confidence: 99%
“…Bowel obstruction is a common cause of hospitalization and among the most common indications for surgery in the United States but is a rare cause of ICU admission. 20 Mechanical obstruction of the small bowel is typically caused by extrinsic compression. In the United States, the most common cause is intra-abdominal adhesions from prior surgery while worldwide the most common etiology of small bowel obstruction is incarcerated hernia.…”
Section: Intestinal Obstructionmentioning
confidence: 99%
“…Bowel obstruction is a common cause of hospitalization and among the most common indications for surgery in the United States but is a rare cause of ICU admission 20. Mechanical obstruction of the small bowel is typically caused by extrinsic compression.…”
Section: Gastroenterological Surgical Emergenciesmentioning
confidence: 99%